2013
DOI: 10.3390/molecules181215255
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure-Activity Relationships of Novel Ecdysteroid Dioxolanes as MDR Modulators in Cancer

Abstract: Ecdysteroids, molting hormones of insects, can exert several mild, non-hormonal bioactivities in mammals, including humans. In a previous study, we have found a significant effect of certain derivatives on the ABCB1 transporter mediated multi-drug resistance of a transfected murine leukemia cell line. In this paper, we present a structure-activity relationship study focused on the apolar dioxolane derivatives of 20-hydroxyecdysone. Semi-synthesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 12 publications
4
34
0
Order By: Relevance
“…The studied cell lines included both drug susceptible (breast: MCF-7, prostate: PC3 and LNCaP, epidermal: KB-3-1 and murine lymphoma: L5178) and multi-drug resistant (MDR) ones obtained either by transfection with the human ABCB1 transporter (L5178 MDR ) or by stepwise adaptation to a chemotherapeutic agent (MCF-7 Dox to doxorubicin, KB-C-1 to colchicine). [6][7][8][9] The compounds were identified as weak to mild inhibitors of ABCB1 function, and this activity was only marginally correlating with their very strong chemosensitizing activity observed on ABCB1 over-expressing cancer cells such as L5178 MDR . 6,8 Moreover, a less pronounced, but still significant chemo-sensitization was also observed on cancer cell lines with minimal or no detectable ABCB1 expression, suggesting the involvement of mechanisms other than the inhibition of efflux pump function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studied cell lines included both drug susceptible (breast: MCF-7, prostate: PC3 and LNCaP, epidermal: KB-3-1 and murine lymphoma: L5178) and multi-drug resistant (MDR) ones obtained either by transfection with the human ABCB1 transporter (L5178 MDR ) or by stepwise adaptation to a chemotherapeutic agent (MCF-7 Dox to doxorubicin, KB-C-1 to colchicine). [6][7][8][9] The compounds were identified as weak to mild inhibitors of ABCB1 function, and this activity was only marginally correlating with their very strong chemosensitizing activity observed on ABCB1 over-expressing cancer cells such as L5178 MDR . 6,8 Moreover, a less pronounced, but still significant chemo-sensitization was also observed on cancer cell lines with minimal or no detectable ABCB1 expression, suggesting the involvement of mechanisms other than the inhibition of efflux pump function.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The compounds were identified as weak to mild inhibitors of ABCB1 function, and this activity was only marginally correlating with their very strong chemosensitizing activity observed on ABCB1 over-expressing cancer cells such as L5178 MDR . 6,8 Moreover, a less pronounced, but still significant chemo-sensitization was also observed on cancer cell lines with minimal or no detectable ABCB1 expression, suggesting the involvement of mechanisms other than the inhibition of efflux pump function. 9 Nevertheless, ABCB1 is a potential target particularly in cancer stem cells (CSCs): over-expression of this transporter is not only an important mechanism for the chemo-resistance of CSCs, 10 but it has also been found to be closely associated to stem-likeness in non-small cell lung cancer whose stem-like properties could be overcome by ABCB1 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Lipophilicity of several ecdysteroids was determined using reversed-phase thin-layer chromatography, giving in the order of decreasing R M values such as cyasterone, 22-deoxy-20-hydroxyecdysone, 2-deoxyecdysone, viticosterone E, makisterone A, 22-deoxy-20-hydroxyecdysone, 20-hydroxyecdysone 22 acetate, rubrosterone, polypodine B, 20-hydroxyecdysone, and integristerone A [9]. Martins et al described that less polar ecdysteroid derivatives, in particularly those with substituted dioxolane rings at positions 2,3 and 20,22 like, for example, diacetonides, can exert a strong chemo-sensitizing activity on various cancer cell lines including drug-sensitive as well as multidrug-resistant ones [10][11][12]. In a most recent study by Müller et al (Eur.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that non-polar ecdysteroids possess chemo-sensitizing activity towards various cancer cell lines [7][8][9][10]. The fluorination of steroids, juvenile hormones, and pheromones can influence the biological activity of these compounds [11].…”
Section: Introductionmentioning
confidence: 99%